2018
DOI: 10.1177/0093650218796363
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and Sexual Behavior: Do Sexual Attitudes Mediate or Confound?

Abstract: Using four separate national probability metasamples of adults in the United States, two measures of pornography consumption, two measures of sexual attitudes, and two measures of sexual behavior, this article pits two macrotheories on pornography and its behavioral effects against each other in competing, falsifiable hypothesis tests. Specifically, the article compares the libertarian theory of pornography’s hypothesis that sexual attitudes are a confound of the pornography consumption—sexual behavior relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 111 publications
0
9
0
3
Order By: Relevance
“…Specifically, having been socialised in a sexually liberated climate could have influenced the individual to develop liberal sexual practices. It is also likely that the openness in the media about sex, and the easy access to pornography on the Internet, have encouraged experimentation with new sexual practices, normalised behaviours, by changing sexual attitudes (Wright, 2020). Furthermore, most participants in this study had their most recent sexual intercourse with a committed partner, and the availability of a committed partner will affect the type of social environment the sex takes place in, and the degree to which those who interact sexually feel safe and self-secure.…”
Section: Age/cohort Effectsmentioning
confidence: 99%
“…Specifically, having been socialised in a sexually liberated climate could have influenced the individual to develop liberal sexual practices. It is also likely that the openness in the media about sex, and the easy access to pornography on the Internet, have encouraged experimentation with new sexual practices, normalised behaviours, by changing sexual attitudes (Wright, 2020). Furthermore, most participants in this study had their most recent sexual intercourse with a committed partner, and the availability of a committed partner will affect the type of social environment the sex takes place in, and the degree to which those who interact sexually feel safe and self-secure.…”
Section: Age/cohort Effectsmentioning
confidence: 99%
“…In addition to sex drive, calls have been made for the inclusion of common audience attributes that may confound analyses (Vega & Malamuth, 2007). Three commonly proposed confounds in the pornography effects literature are age, education, and ethnicity (Wright, 2020a).…”
Section: Studies Testing Pornography and Sexual Aggressionmentioning
confidence: 99%
“…Furthermore, research has pointed at the possibility that sexual attitudes can also be seen as confounds in the relationship between pornography use and sexual behavior, predicting both higher pornography use as well as the sexual behavior. A recent study comparing a sexual-script-based prediction to a confounding prediction showed that the model looking at sexual attitudes as confounds did not hold and that the prediction of sexual behavior by pornography use remains after controlling for confounds such as sexual attitudes (Wright, 2018). That said, other confounding factors, such as peer norms, family functioning, or personality factors such as hypergender orientations or sensation seeking, may influence both pornography use as well as the willingness to engage in NCFS.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%